AKTIVITAS ANTIOKSIDAN DAN PENGHAMBATAN α-GLUKOSIDASE OLEH EKSTRAK ETANOL BAKTERI ASAM LAKTAT INDIGENUS - Eko Farida; Betty Sri Laksmi Jenie; Lilis Nuraida; Puspo Edi Giriwono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Lactic acid bacteria (LAB) are one of Indonesia's biodiversity which can be beneficial for food and health purposes. Some of LAB are potential probiotics with specific functional properties, such as antidiabetes. This study evaluated the effect of ethanol extracts of twelve indigenous LAB in inhibiting α-glucosidase enzyme and their antioxidant activities. Assay for the α-glucosidase inhibition was performed on LAB ethanol extract using spectrophotometric method at λ=410 nm, while the antioxidant activity was measured using 1,1-diphenyl-2-picrylhydrazyl (DPPH) method at λ=517 nm. The results showed that α-glucosidase inhibition was significantly different between the isolates (P<0.01). Lactobacillus fermentum S21209 had the highest α-glucosidase inhibition activity, which was significantly different from Lactobacillus plantarum MB427, Lactobacillus plantarum Pi28a, Lactobacillus delbrueckii W24802 and Lactobacillus plantarum 2 W22409. Evaluation of the antioxidant activity also showed significant difference between the isolates (P<0.01). Lactobacillus plantarum BSL had the highest antioxidant activity (92.81±1.36%), which was not significantly different from vitamin C as a control. This preliminary study reported that twelve indigenous LAB could be used as potential antidiabetic probiotics, although the responsible compounds are not known.